On the Avenue of the Mystery The Postwar Counterculture in Novels and Film - Hentzi, Gary (Taylor & Francis, 2023)
This volume is a study of eight major novels from the postwar period (1945-65) in conjunction with the films made from them during a later period of a little less than three decades straddling the millennium (1985-2012). The comparison of these novels (by Ken Kesey, Paul Bowles, Carson McCullers, Jack Kerouac, James Baldwin, Alexander Trocchi, William Burroughs, and Peter Matthiessen) with their film adaptations offers the opportunity for a historical reassessment not only of the novels themselves but also of the global counterculture of the years 1965-75, which they prefigure in a variety of ways. Appearing more than a decade after the waning of the counterculture and in some cases as much as fifty years after the novels on which they are based, the films display significant revisions and omissions prompted by the historical and cultural changes of the intervening years. Whereas these changes are nowadays often interpreted in purely political terms, this book argues that the religious theme of mystery and its decline is central to the novels and films and is a key feature of the period of cultural transformation that they bookend. At once a work of literary criticism, film studies, and cultural history, this text has the potential to reach both an academic audience and the broader readership that has long existed for these novels as well as the even broader one interested in reappraising the period of the global counterculture-among the most important of the influences that have shaped the contemporary world.